Project-based Learning in a Geomatics Bachelor Program: A Digital Heritage Preservation Project - A. Ladai (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Like in most bachelor engineering programs, the education of geomatics students typically begins with an extensive theoretical introduction covering fundamental subjects. The general objective of the bachelor program is to cultivate geomatics engineers with robust hands-on knowledge. Nevertheless, the progression to a stage where students can independently engage in exercises with minimal supervision is a long process. Although field work-based practices are dominant in this field, they often entail activities limited to testing, experimenting, and the application of basic theories. While this approach is efficient in imparting routine knowledge, it may lead to the fragmentation of acquired knowledge, thereby lacking a comprehensive understanding of the broader significance and context. Students often encounter more complex challenges when commencing work on their bachelor thesis, leading to a steep learning curve within a constrained timeframe. This late exposure to real-world tasks can be a limiting factor, hindering a smoother transition from education to professional work. This paper provides a case study of project-based learning (PjBL) within a geomatics bachelor program. Specifically, it discusses a digital heritage preservation project where students documented an old Norwegian log house throughout the autumn semester of 2023. The outcomes of this learning approach are analyzed with the help of the key features of the PjBL methodology, focusing on students' learning outcomes and their assessment measures.